The regulation of genetically modified organisms on a local level: exploring the determinants of cultivation bans - Hartung, Ulrich; Bulian, Simon (Sustainability, 2018)
This study investigates municipalities' regulatory activities in the field of Genetically Modified Organisms (GMOs) for agricultural use. To explore the determinants of these activities, the case of Germany was selected as in this country, municipalities have legal possibilities to impose local GMO cultivation bans. Using data from 131 local council resolutions, the combination of qualitative and quantitative content analysis shows that, in most cases, no single factors, but a variety of factors lead to regulatory activity. The study reveals that functional motivations to prevent negative socio-economic effects or impacts on the environment or human health are decisive for municipalities’ decisions to regulate. Furthermore, the results of the quantitative analysis unveil that municipalities often refer to both socio-economic reasons and risks for the environment and human health when justifying their decisions. Moreover, the results indicate that local policymakers impose popular cultivation bans to promote their own political success. Finally, the horizontal diffusion of regulations between municipalities, but also vertical diffusion from higher political levels can be observed. Overall, the results of this study on GMOs on a local level further emphasize the importance of analyzing the interdependencies between agroecosystems and socio-economic systems in their full complexity.